CASHBACK: FEATURES OF THE MARKETING ACTIVITIES OF THE BANKING SPHERE - E. Butenko; I. Chernikov (Вестник Северо-Кавказского федерального университета)
Marketing is a complex mechanism that involves a fairly large number ofpeople. It includes features such as buying, selling, investing, risk accounting, standardization, and more. Support for each function is very important for all parties to trade. And not only the number of sales, but also the number of satisfied customers from the purchase will depend on the chosen financial policy. The banking sector is no exception and is actively using modern marketing to promote its activities. In the conditions of constant competition, the one who chooses the most winning position will have a greater client base. And one of the ways to ensure decent competition is the reward system, which includes cashback, discounts and bonuses. Proper combination of these strategies will ensure the most faithful business planning of any company.